Envelope Conformational Changes Induced by Human Immunodeficiency Virus Type 1 Attachment Inhibitors Prevent CD4 Binding and Downstream Entry Events - Ho, Hsu-Tso (American Society for Microbiology, 2006)
BMS-488043 is a small-molecule human immunodeficiency virus type 1 (HIV-1) CD4 attachment inhibitor with demonstrated clinical efficacy. The compound inhibits soluble CD4 (sCD4) binding to the 11 distinct HIV envelope gp120 proteins surveyed. Binding of BMS-488043 and that of sCD4 to gp120 are mutually exclusive, since increased concentrations of one can completely block the binding of the other without affecting the maximal gp120 binding capacity. Similarly, BMS-488043 inhibited virion envelope trimers from binding to sCD4-immunoglobulin G (IgG), with decreasing inhibition as the sCD4-IgG concentration increased, and BMS-488043 blocked the sCD4-induced exposure of the gp41 groove in virions. In both virion binding assays, BMS-488043 was active only when added prior to sCD4. Collectively, these results indicate that obstruction of gp120-sCD4 interactions is the primary inhibition mechanism of this compound and that compound interaction with envelope must precede CD4 binding. By three independent approaches, BMS-488043 was further shown to induce conformational changes within gp120 in both the CD4 and CCR5 binding regions. These changes likely prevent gp120-CD4 interactions and downstream entry events. However, BMS-488043 could only partially inhibit CD4 binding to an HIV variant containing a specific envelope truncation and altered gp120 conformation, despite effectively inhibiting the pseudotyped virus infection. Taken together, BMS-488043 inhibits viral entry primarily through altering the envelope conformation and preventing CD4 binding, and other downstream entry events could also be inhibited as a result of these induced conformational changes.